Association of Anti–Topoisomerase I Antibodies of the IgM Isotype With Disease Progression in Anti–Topoisomerase I–Positive Systemic Sclerosis. Issue 11 (29th September 2020) - Boonstra, Maaike; Bakker, Jaap A.; Grummels, Annette; Ninaber, Maarten K.; Ajmone Marsan, Nina; Wortel, Corrie M.; Huizinga, Tom W. J.; Jordan, Suzana; Hoffman‐Vold, Anna‐Maria; Distler, Oliver; Toes, René E. M.; Scherer, Hans Ulrich; et al.
Abstract : Objective: Anti–topoisomerase I (anti–topo I) autoantibodies in systemic sclerosis (SSc) are associated with diffuse skin involvement and interstitial lung fibrosis. Thus far, however, the relationship between anti–topo I antibody response and disease course has not yet been fully evaluated. This study was undertaken to gain insight into the association between characteristics of the anti–topo I antibody response and clinical disease course in SSc patients positive for anti–topo I antibodies. Methods: Levels of anti–topo I IgG, anti–topo I IgM, and anti–topo I IgA were assessed in consecutive serum samples obtained from patients at baseline who were positive for anti–topo I IgG in the Leiden Combined Care In Systemic Sclerosis (CCISS) cohort. One‐year disease progression was defined by a relevant increase in modified Rodnan skin thickness score (MRSS), decline in pulmonary function, development of digital ulcers, renal crisis, and pulmonary hypertension, and/or mortality. Validation was performed in SSc patients who were positive for anti–topo I from the Oslo University Hospital and University Hospital Zurich. Results: Of the 103 patients with anti–topo I IgG in the CCISS cohort, clinical data were available to assess 1‐year disease progression in 81 patients. Of these 81 patients, 23 (28%) had disease progression. At baseline, patients with disease progression were significantly more often anti–topo I IgM–positive than those who did not experience disease progression (21 [91%] of 23 versus 33 [57%] of 58; P < 0.01). This finding was confirmed in the independent validation samples. Conclusion: In SSc patients who were anti–topo I IgG–positive, presence of anti–topo I IgM, which might be considered as a surrogate for an ongoing autoreactive B cell immune response, is associated with disease progression.